2019
DOI: 10.7759/cureus.5552
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of Unknown Primary: A Review on Clinical Guidelines in the Development and Targeted Management of Patients with the Unknown Primary Site

Abstract: Cancer of unknown primary (CUP) is a malignant widespread metastatic disease without an identifiable primary site after extensive clinical investigation. Recently, a decline is observed in the diagnosis of CUP, mainly due to improvement in detection of the primary tumors, thus decreasing the unknown primaries. Worldwide, CUP is the sixth to eighth most common malignancy, accounting for 2.3% to 5% of a new cancer diagnosis. CUP is third to fourth most common cause of death due to cancer-related mortality. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 24 publications
1
74
0
5
Order By: Relevance
“…Recent studies have found that these unclassifiable neoplasms represent a heterologous group of tumors [18]. Many specific entities have been recently identified with new molecular and/or immunohistochemical tools, especially in the head and neck region [21][22][23][24][25]. Identification of these new entities is important for us to understand the epidemiology, etiology, tumor behavior, and most importantly, identify effective patient treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that these unclassifiable neoplasms represent a heterologous group of tumors [18]. Many specific entities have been recently identified with new molecular and/or immunohistochemical tools, especially in the head and neck region [21][22][23][24][25]. Identification of these new entities is important for us to understand the epidemiology, etiology, tumor behavior, and most importantly, identify effective patient treatment [26].…”
Section: Discussionmentioning
confidence: 99%
“…The pathobiology of CUP remains to be elucidated; however, two hypotheses have been described to explain their inception. The first theory establishes that a tumor can develop without a premalignant lesion or primary tumor (10,11). The second theory postulates that metastatic progression occurs parallel to development of the primary lesion emphasizing that CUP metastases may be a premature event in tumorigenesis (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…The first theory establishes that a tumor can develop without a premalignant lesion or primary tumor (10,11). The second theory postulates that metastatic progression occurs parallel to development of the primary lesion emphasizing that CUP metastases may be a premature event in tumorigenesis (10,11). Regardless of etiology, histological confirmation of a metastatic tumor is the fundamental basis of a diagnosis of CUP.…”
Section: Discussionmentioning
confidence: 99%
“…Ist sowohl in der Bildgebung als auch der Endoskopie kein Tumor zu lokalisieren, sollte noch bevor systematische Biopsien erfolgen ein FDG-PET/ CT (▶ Abb. 9) durchgefĂŒhrt werden [18]. FĂŒr die FDG-PET/CT wurde die Tumordetektionsrate, SensitivitĂ€t und SpezifitĂ€t in einer Metaanalyse mit 44 %, 97 % und 68 % angegeben [19].…”
Section: Karzinome Unbekannten Ursprungsunclassified
“…KrĂ€ftige FDG-Aufnahme sowohl im PrimĂ€rtumor, als auch in den Lymphkontenmetastasen. 18 F-FDG PET, CT nativ , fusioniertes 18…”
unclassified